Critical factors influencing effective of ICT resources and capabilities - Mohamed, Hany; Ibrahim, Adamu Abubakar; Zeki, Akram M. (Journal of Theoretical and Applied Information Technology(JATIT), 2018)
Substantial research on the importance of strategic Information and Communication Technology (ICT) resources and capabilities for higher institution has mainly focused on developed countries. The results of these studies may not hold for developing nations and in particular, the Kingdom of Saudi Arabia (KSA). To address this gap, this research therefore, builds on theory of DeLone and McLean to examine the strategic links between the success of effective utilization of ICT Resources and ICT Capabilities of KSA higher institutions. Quantitative research methodology has been used. The study was conducted in a KSA context from a sample of 68 higher institutions. Nine main hypotheses were formulated and tested. Analysis of the data provided support for all the nine main hypotheses, except for relationship between “User Involvement and Effective utilization of ICT resources and capabilities